Tracking supermassive black hole mergers from kpc to sub-pc scales with AXIS - Foord, Adi; Cappelluti, Nico; Liu, Tingting; Volonteri, Marta; Habouzit, Mélanie; Pacucci, Fabio; Marchesi, Stefano; Chen, Nianyi; Di Matteo, Tiziana; Mallick, Labani; Koss, Michael (Universe, 2024)
We present an analysis showcasing how the Advanced X-ray Imaging Satellite (AXIS), a proposed NASA Probe-class mission, will significantly increase our understanding of supermassive black holes undergoing mergers—from kpc to sub-pc scales. In particular, the AXIS point spread function, field of view, and effective area are expected to result in (1) the detection of hundreds to thousands of new dual AGNs across the redshift range 0
Gesehen am 28.02.2025